Health literacy about cancer prevention and control and its influencing factors among urban and rural residents in Hebei province - Ya-hui HAO; Dao-juan LI; Shuo ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the status and influencing factors of health literacy about cancer prevention and control among urban and rural residents of Hebei province for providing reference to the popularization of cancer prevention and control knowledge in the population. MethodsWith the questionnaire developed by National Cancer Institute and China Health Education Center and stratified random sampling, face-to-face interviews were conducted among 6 000 permanent residents aged ≥ 15 years in 16 districts/counties of Hebei province during May - June 2021. ResultsOf the 5847 participants with valid responses, 3 921 (67.06%) were assessed as being with health literacy about cancer prevention and control and the proportion of being with the health literacy was 60.50% and 71.73% for the male and female participants, 71.83% and 58.62% for the urban and rural participants. Multivariate binary logistic regression analysis showed that the participants with following characteristics are more likely to have the health literacy about cancer prevention and control: female gender, with the education of middle school and above, married, being mental worker other than medical personnel, being medical worker, with occupations other than mental/manual/medical worker, with a self-reported fair or good health status, and with family cancer history; while, the participants living in rural regions are less likely to have the health literacy. ConclusionThe health literacy about cancer prevention and control was at a high level relatively and mainly influenced by gender, marital status, education, occupation, living region, self-rated health, and family cancer history among urban and rural residents of Hebei province.